Corporate Tax Integrity and Financial Constraints: Evidence from China. Issue 3 (19th February 2023) - Wang, Pin; Xie, Linlin; Zhu, Gege; Guan, Yu
ABSTRACT: This study examines how corporate tax integrity affects financial constraints. In the past, scholars have captured corporate's trust in an indirect way, and our paper fills this void. To capture the earned trust of enterprises in a more direct way, we use a firm's tax integrity level as a proxy for its earned trust. Our results show that corporate tax integrity is negatively related to financial constraints. Further, we examine whether social trust in the regions where the corporate is located will affect the relationship between firm's tax integrity and financial constraints, the result suggests that corporate tax integrity has a stronger effect on financing constraints of firms located in high social trust regions. Finally, we further find that firms' business risk is a channel where corporate tax integrity affects financial constraints.